2012
DOI: 10.1093/jxb/err431
|View full text |Cite
|
Sign up to set email alerts
|

A R2R3-type MYB gene, OsMYB2, is involved in salt, cold, and dehydration tolerance in rice

Abstract: MYB-type transcription factors play a diverse role in plant development and response to abiotic stress. This study isolated a rice R2R3-type MYB gene, OsMYB2, and functionally characterized its role in tolerance to abiotic stress by generating transgenic rice plants with overexpressing and RNA interference OsMYB2. Expression of OsMYB2 was up-regulated by salt, cold, and dehydration stress. OsMYB2 was localized in the nucleus with transactivation activity. No difference in growth and development between the OsM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
438
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(460 citation statements)
references
References 53 publications
(97 reference statements)
21
438
0
1
Order By: Relevance
“…However, the OsMYB4 network was independent of the DREB/CBF pathway (Park et al, 2010). In addition, several members belonging to the MYB family, including OsMYB2 (Yang et al, 2012), OsMYB511 , CMYB1 , and OsMYB48-1 (Xiong et al, 2014), also were reported for their roles in cold stress regulation, but their molecular mechanisms have not been clearly revealed.…”
mentioning
confidence: 99%
“…However, the OsMYB4 network was independent of the DREB/CBF pathway (Park et al, 2010). In addition, several members belonging to the MYB family, including OsMYB2 (Yang et al, 2012), OsMYB511 , CMYB1 , and OsMYB48-1 (Xiong et al, 2014), also were reported for their roles in cold stress regulation, but their molecular mechanisms have not been clearly revealed.…”
mentioning
confidence: 99%
“…For instance, salt-tolerant alfalfa plants roots accumulate two-fold more proline than the salt-sensitive plants [134,135]. Additionally, different strategies used to develop transgenic rice plants that accumulate proline and soluble sugars resulted in plants that were protected against drought and osmotic stress [136][137][138].…”
Section: Improving Abiotic Stresses Tolerance In Crop Cultivarsmentioning
confidence: 99%
“…MYB-core binding sites (T/ CAACNA/G) and MYC-core recognition sites (CANNTG) were noted in the region. Both have been shown to play important roles in plant responses to salt, low temperature, and drought (Miura et al, 2012;Yang et al, 2012;Feng et al, 2013;Su et al, 2014). Furthermore, several hormones could influence the relevant promoter element .…”
Section: Cloning Of the 5'-flanking Region Of The Gpat Gene From Lilimentioning
confidence: 99%